Crystal structure of N-isopropyl-1,8-naphthalimide C15H13NO2 - He Weifeng; Liu Yingfan; Bi Jingjing (Zeitschrift für Kristallographie - New Crystal Structures)
C15H13NO2, orthorhombic, Cmce (no. 64), a = 7.0048(4) Å, b = 18.0939(7) Å, c = 19.2281(8) Å, V = 2437.0 Å3, Z = 8, Rgt(F) = 0.0614, wRref(F2) = 0.1989, T = 293.9(10) K.